2003
DOI: 10.1034/j.1600-0749.2003.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanin as a Target for Melanoma Chemotherapy: Pro‐oxidant Effect of Oxygen and Metals on Melanoma Viability

Abstract: Melanoma cells have a poor ability to mediate oxidative stress, which may be attributed to constitutive abnormalities in their melanosomes. We hypothesize that disorganization of the melanosomes will allow chemical targeting of the melanin within. Chemical studies show that under oxidative conditions, synthetic melanins demonstrate increased metal affinity and a susceptibility to redox cycling with oxygen to form reactive oxygen species. The electron paramagnetic resonance (EPR)-active 5,5¢-dimethyl-pyrollidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…Previous speciation characterization had suggested that an oxidized species within the melanin, a quinone imine, could serve as a powerful metal chelator (Spoganicz 2002), and this might then enhance the pro-oxidant generation of ROS. Importantly, the ROS generated by the synthetic melanin behaved in the same manner as the melanoma cell lines, in that exogenous catalase quenched the signal but superoxide dismutase greatly enhanced the signal (Farmer 2003); and using the EPR and DNA clipping assays, the similar phenomenon as described above was demonstrated with intact melanoma cells, reconfirming the initial luminescence experiments. These results suggested that melanin in melanocytes became pro-oxidant during the transformation process; utilizing the idea that metals may enhance this behavior, we have designed a number of lipophilic chelators (Farmer et al 2005) as candidate chemotherapeutic drugs.…”
Section: Redox Status Of Melanocytes and Melanoma Cellssupporting
confidence: 63%
See 1 more Smart Citation
“…Previous speciation characterization had suggested that an oxidized species within the melanin, a quinone imine, could serve as a powerful metal chelator (Spoganicz 2002), and this might then enhance the pro-oxidant generation of ROS. Importantly, the ROS generated by the synthetic melanin behaved in the same manner as the melanoma cell lines, in that exogenous catalase quenched the signal but superoxide dismutase greatly enhanced the signal (Farmer 2003); and using the EPR and DNA clipping assays, the similar phenomenon as described above was demonstrated with intact melanoma cells, reconfirming the initial luminescence experiments. These results suggested that melanin in melanocytes became pro-oxidant during the transformation process; utilizing the idea that metals may enhance this behavior, we have designed a number of lipophilic chelators (Farmer et al 2005) as candidate chemotherapeutic drugs.…”
Section: Redox Status Of Melanocytes and Melanoma Cellssupporting
confidence: 63%
“…Subsequently, an electrochemical model of eumelanin (dihydroxyindole polymerized on a graphite surface) (Gidanian et al 2002) and was used to measure ROS generation, as measured by spin trapping molecules of superoxide and hydroxyl radicals. It was demonstrated that exposure of synthetic eumelanin to oxygen led to that the generation of ROS, markedly enhanced by the addition of transition metals (Farmer et al 2003). Previous speciation characterization had suggested that an oxidized species within the melanin, a quinone imine, could serve as a powerful metal chelator (Spoganicz 2002), and this might then enhance the pro-oxidant generation of ROS.…”
Section: Redox Status Of Melanocytes and Melanoma Cellsmentioning
confidence: 99%
“…[51][52][53] In addition, in melanoma the transformation causes damage of melanosomes and thereby enhances reactive oxygen species production, increasing vulnerability of cells to oxidative stress. 54 However, two other melanoma cell lines studied (S91 and Sk-mel188) were much more resistant to treatment with H 2 O 2 , indicating that sensitivity to oxidative stress is cell-type-dependent.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings concerning Cu, when exposure was categorized into two categories, must be evaluated with caution, also considering that there was limited evidence of a linear association between toenail levels and disease risk. Despite these caveats, in view of the established ability of Cu to induce oxidative stress, a possible pathogenetic mechanism of melanoma (Farmer et al, 2003;Sander et al, 2004), an association between excess Cu exposure and melanoma risk should also be considered to explain our findings. Our findings might also be explained by an abnormal metabolism of this element, since in melanoma patients it has been described as an abnormal expression of metallothioneins, ubiquitous proteins with high affinity for metals such as Cu, whose higher concentrations might increase body content of this element (Weinlich et al, 2003).…”
Section: Discussionmentioning
confidence: 99%